Artistic irritations within enterprises: possible applications, impact and potential inspiration - Fenkart, Susanne (Momentum Quarterly, 2014)
With respect to the idea of progress the article deals with possibilities of artistic irritations in the economy. Art enables an examination of established constructions and experimentation with different perspectives, which are normally not accessible to the system. Exemplarily three case studies are told: The first example is dedicated to the art concept of the consultancy Droege Group. The economic way to deal with art is carved out, simultaneously it attempts to find resulting irritations. In contrast the second case study shows an artist’s view: The project “8 x 5 x 363 + 1” of the artist Raphaëlle De Groot reflects the daily working routine in a cloth factory. The project is presented and the artistic contribution to the advancement of the enterprise is discussed. Third possibility is the artistic irritation as pure artwork: The work “The Trainee” of the artist Pilvi Takala deals with basic conditions of contemplation in enterprises as well as conventions and borders of social communities. Aim of the talk is to point out the impact of artistic irritations and to initiate contemplation about possible potentials.
Keywords: systems theory; artistic irritations in enterprises; artistic interventions in enterprises; qualitative social research; case studies